Cyber risks and insurance : the legal principles. - Qc, dean armstrong. steward, thomas. thakerar, shyam (London, England : Zed Books, 2020)
"Full of tips, case studies, tables and checklists this new title sets out the parameters of liability in respect of potential and actual cyber insurance claims and examines the significant areas where such claims will have the greatest impact. Covering First and Third party insurance, it provides the answers to questions such as: What is the extent to which a data breach can be protected or mitigated against by having suitable insurance in place? How does having insurance interplay with obligations under the GDPR? To what extent can insurance be used to safeguard driverless cars, drones and other AI-machines? How can insurance companies assist when hackers hold companies to ransom after stealing data? How can insurance assist with smart contracts on the blockchain and for potential coding errors? How can insurance mitigate against the hacking of online systems of manned ships?."--
Chapter 1; Introduction -- Chapter 2: Data Obligations and Breaches Generally -- Chapter 3: The Data Protection Regime as it Applies to Insurance -- Chapter 4: AI Based Insurance -- Chapter 5: Cyber Extortion -- Chapter 6; Terrorism Insurance after a Cyber Attack -- Chapter 7: Cyber Insurance and the Blockchain -- Chapter 8: Cyber Issues in Shipping -- Chapter 9: Remedies -- Chapter 10: Cyber Fraud in International Trade -- Chapter 11: War Exclusion/General Exclusion Clauses -- Chapter 12: Insuring Ransom Payments Resulting from Piracy in Somalia -- Chapter 13: Business Interuption -- Chapter 14: Cyber Issues in Energy
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Computer networks -- Law and legislation; Computer insurance; Law,Insurance law; Electronic books